1997
DOI: 10.1523/jneurosci.17-19-07330.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Modulation of Sodium Current in Hippocampal Neurons via cAMP-Dependent Phosphorylation of Specific Sites in the Sodium Channel α Subunit

Abstract: Phosphorylation of brain Na ϩ channel ␣ subunits by cAMPdependent protein kinase (PKA) decreases peak Na ϩ current in cultured brain neurons and in mammalian cells and Xenopus oocytes expressing cloned brain Na ϩ channels. We have studied PKA regulation of Na ϩ channel function by activation of D1-like dopamine receptors in acutely isolated hippocampal neurons using whole-cell voltage-clamp recording techniques. The D1 agonist SKF 81297 reversibly reduced peak Na ϩ current in a concentration-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
134
2
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 40 publications
(53 reference statements)
17
134
2
1
Order By: Relevance
“…Similarly, we found that application of 0.5 μM Ro-31-8425 application blocked an increase in Nav1.8 currents induced by either 8-Br-cAMP or the cAMP analogue forskolin [23]. This was supported by the fact that application of a PKC inhibitor (staurosporine or PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ) caused a marked inhibition of the forskolin-induced increase in the G V1/2 base (i.e. the percentage change in G at baseline V 1/2 ) [24,36,46].…”
Section: Modulation Of Nav18 Currents By Pkcsupporting
confidence: 56%
See 2 more Smart Citations
“…Similarly, we found that application of 0.5 μM Ro-31-8425 application blocked an increase in Nav1.8 currents induced by either 8-Br-cAMP or the cAMP analogue forskolin [23]. This was supported by the fact that application of a PKC inhibitor (staurosporine or PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ) caused a marked inhibition of the forskolin-induced increase in the G V1/2 base (i.e. the percentage change in G at baseline V 1/2 ) [24,36,46].…”
Section: Modulation Of Nav18 Currents By Pkcsupporting
confidence: 56%
“…The application of the PKC inhibitor PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] significantly suppresses the forskolin-induced increase in the Nav1.8 current but the PKA inhibitor WIPTIDE has no significant effect on the PKC activator phorbol12, 13-dibutyrate (PDBu)-induced increase in the current [36]. When considering these results together, it is possible that PKCinduced phosphorylation of the channel protein at serine 1506 is required to enable PKA-induced phosphorylation of other sites on the channel protein suggested by Li et al [40] in a relationship between PKC and PKA on the convergent regulation of Na + channels.…”
Section: Interaction Between Pkc and Pka On Nav 18 Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular dopamine levels are low in dim conditions and are high in bright conditions (Boatright et al, 1989). Because the activity of voltage-gated sodium channels in other parts of the CNS is modulated by dopamine (Cantrell et al, 1997;Hayashida and Ishida, 2004), and dopamine receptors are present on bipolar cells (Veruki and Wassle, 1996;NguyenLegros et al, 1997;Mora-Ferrer et al, 1999), we investigated whether dopamine mediated the light-dependent modulation of the sodium channel activity by activating dopamine receptors in dim light with agonist applications.…”
Section: Dopamine Mimicked the Effects Of Light On Voltage-gated Sodimentioning
confidence: 99%
“…Voltage-gated sodium channels are regulated by G-protein-coupled receptor (GPCR)-mediated phosphorylation (for review, see Cantrell and Catterall, 2001). Dopamine (Surmeier et al, 1992;Ma et al, 1994;Cantrell et al, 1997;Cantrell et al, 1999) and serotonin (Carr et al, 2003) modulate the generation of sodium spikes. However, it was not known whether EPSP amplification by sodium channels is affected by GPCR activation.…”
Section: Dopamine and Bright Light Contribute To Network Adaptation Bmentioning
confidence: 99%